2014
DOI: 10.1186/s13045-014-0057-5
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors in the pathogenesis of human B cell malignancies

Abstract: Toll-like receptors (TLRs) are important players in B-cell activation, maturation and memory and may be involved in the pathogenesis of B-cell lymphomas. Accumulating studies show differential expression in this heterogeneous group of cancers. Stimulation with TLR specific ligands, or agonists of their ligands, leads to aberrant responses in the malignant B-cells. According to current data, TLRs can be implicated in malignant transformation, tumor progression and immune evasion processes. Most of the studies f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 69 publications
0
37
0
1
Order By: Relevance
“…Liang et al (2008) [24] stated that human B-ALL cell lines and primary B-ALL cells express high levels of TLR-7 mRNA and proteins. Also, Isaza-Correa et al (2014) [12] reported that in ALL cell lines, TLR-1, TLR-2, TLR-3, TLR-4, TLR-6 and TLR-7 are expressed albeit at variable levels. Although Bourke et al (2003) [15] reported that normal and malignant B cells show a distinct TLR mRNA expression profile, which includes particularly high levels of TLR-9 and TLR-10, a limited study by Reid et al (2005) suggested a lack …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liang et al (2008) [24] stated that human B-ALL cell lines and primary B-ALL cells express high levels of TLR-7 mRNA and proteins. Also, Isaza-Correa et al (2014) [12] reported that in ALL cell lines, TLR-1, TLR-2, TLR-3, TLR-4, TLR-6 and TLR-7 are expressed albeit at variable levels. Although Bourke et al (2003) [15] reported that normal and malignant B cells show a distinct TLR mRNA expression profile, which includes particularly high levels of TLR-9 and TLR-10, a limited study by Reid et al (2005) suggested a lack …”
Section: Discussionmentioning
confidence: 99%
“…In ALL cell lines, TLR-1, TLR-2, TLR-3, TLR-4, TLR-6 and TLR-7 are expressed albeit at variable levels. In bone marrow of ALL patients with > 90% blasts TLR-2 mRNA can be detected in the majority of the samples [12].…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Nevertheless, emerging evidence suggests that TLR may also exert a direct effect on tumor cells and may regulate tumor progression. 28,29 For example, TLR ligands induce CLL cell viability and chemoresistance in a proportion of cases. 19 Furthermore, the unabated stimulation through TLR and/or IL-1R pathways accelerates leukemia progression in a mouse model of CLL.…”
Section: Discussionmentioning
confidence: 99%
“…3 Toll-like receptors (TLRs) are the fundamental component of the innate immune system and key regulators of acquired immunity. In humans, 10 TLRs proteins (TLR1-10) have been identified, 4 that possess different subcellular localization depending on the specific pathogen-associated molecular patterns or damage-associated molecular patterns they recognize, 5 thus called pattern recognition receptors. TLRs 1, 2, 4, 5, 6, and 10 are found on the extracellular surface of cells, whereas TLRs 3, 7, 8, and 9 are nucleic acid sensors located within the endoplasmic reticulum and endosomes.…”
Section: Introductionmentioning
confidence: 99%